2006
DOI: 10.1212/01.wnl.0000231510.89311.8b
|View full text |Cite
|
Sign up to set email alerts
|

ALS phenotypes with mutations in CHMP2B (charged multivesicular body protein 2B)

Abstract: Abstract-Mutation in the CHMP2B gene has been implicated in frontotemporal dementia. The authors screened CHMP2B in patients with ALS and several cohorts of control samples. They identified mutations (Q206H; I29V) in two patients with non-SOD1 ALS. Neuropathology of the Q206H case showed lower motor neuron predominant disease with ubiquitylated inclusions in motor neurons. Antibodies to p62 (sequestosome 1) showed novel oligodendroglial inclusions in the motor cortex. NEUROLOGY 2006;67:1074-1077 1 Here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
222
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(233 citation statements)
references
References 10 publications
8
222
0
3
Order By: Relevance
“…The p62 protein has been found in intraneuronal or intraglial protein inclusions in a number of neurodegenerative diseases such as Alzheimer (23), Parkinson (21), and Huntington diseases (25,26). More recently, p62 was detected in intraneuronal protein aggregates in ALS with dementia patients (27), in oligodendroglial inclusions in the motor cortex of patients with ALS phenotypes caused by mutations in CHMP2B (28) and in other ALS cases (29). This study is to determine whether and how p62 may contribute to mutant SOD1 aggregation and subsequently ALS etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p62 protein has been found in intraneuronal or intraglial protein inclusions in a number of neurodegenerative diseases such as Alzheimer (23), Parkinson (21), and Huntington diseases (25,26). More recently, p62 was detected in intraneuronal protein aggregates in ALS with dementia patients (27), in oligodendroglial inclusions in the motor cortex of patients with ALS phenotypes caused by mutations in CHMP2B (28) and in other ALS cases (29). This study is to determine whether and how p62 may contribute to mutant SOD1 aggregation and subsequently ALS etiology.…”
Section: Discussionmentioning
confidence: 99%
“…p62 has also been found in protein aggregates in neurodegenerative disorders such as Alzheimer disease (23,24), Huntington disease (25,26), Parkinson disease (21,24) and more recently in ALS. It was found in ALS with dementia (27), in ALS caused by CHMP2B mutations (28) and in other ALS cases (29). However, the role of p62 in mutant SOD1-mediated fALS is currently undocumented.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…[92][93][94][95] In addition, CHMP2B/Vps2B, a subunit of the ESCRT-III complex, was found to be mutated in patients with frontotemporal dementia) and amyotrophic lateral sclerosis. 96,97 Recent publications have shown that autophagy degradation is abrogated in cells depleted of ESCRT subunits or in cells overexpressing a mutant of CHMP2B that caused an accumulation of ubiquitin-protein aggregates. 35,98 Indeed, loss of mSnf7-2, a key component of ESCRT-III that is highly expressed in neurons, caused autophagosome accumulation in cortical neurons, retraction of dendrites and neuronal cell loss.…”
Section: Regulation Of Autophagymentioning
confidence: 99%
“…10 Moreover, a single splice site mutation in CHMP2B, the gene encoding the human ortholog of the yeast ESCRT-III component Vps2, is mutated in a rare form of autosomal dominant frontotemporal dementia (FTD3) and amyotrophic lateral sclerosis (ALS). [11][12][13] However, detailed molecular mechanisms of neurodegeneration associated with FTD remain unknown.…”
mentioning
confidence: 99%